Profile identification in electronic participation tools: a study of the SoPa tool - Mota, Flávio; Paula, Melise; Drummond, Isabela (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2020: Companion Proceedings of the 16th Brazilian Symposium on Information SystemsDO - 10.5753/sbsi.2020.13123, 2020)
Electronic participation (e-participation) tools have emerged as initiatives to allow society to participate in decision-making in public administration. In this context, ways to increase citizen engagement become a problem to be investigated, since it is necessary to have an active participation by citizens. One way is to understand the profile of users of e-participation tools to identify different levels of engagement. This work aims to identify such profiles combining CRM (Customer Relationship Management) strategies and machine learning.